Pengaruh Pendidikan Kesehatan tentang Perawatan Kaki Diabetik terhadap Pengetahuan Perawatan Kaki pada Diabetes Mellitus di RSUP Dr. Soeradji Tirtonegoro Klaten - Andriyanto, Gatot, Arina Maliya, S.Kep., Ns.,M.Si.Med (2017)
Background. One complication in patients with diabetes mellitus due to the lack of health education and foot care. Prevention in patients with diabetes with complications of diabetic neuropathy is foot care. Foot care consists of checking the condition of your feet every day, keeping feet clean, cut nails properly, choosing the right footwear. Good foot care can prevent and reduce the complications of diabetic foot up to 50%. The Purpose Of This Research was to determine the effect of health education on the treatment of diabetic foot to foot care knowledge on diabetes mellitus in Hospital Dr. Soeradji Tirtonegoro Klaten. Research Methods is quasi-experimental designs using a pretest-posttest control group design. The population in this study were 30 respondents were divided into two groups of 15 respondents to the control group and an experimental group of 15 respondents to use accidental sampling. Research Result by Kolmogorov-Smirnov both the control group and the experimental group obtained p-value of 0.20 (p-value> 0.05), which means that the data are normally distributed. Paired T Test results in the control group with a p-value of 0.001 and the experimental group with a p-value of 0.016 subsequent tests Independent T Test was obtained p-value of 0.006 which can be concluded that Ho is refused. Conclusions about the effect of health education on the knowledge of diabetic foot care foot care in people with diabetes mellitus in Hospital Dr. Soeradji Tirtonegoro Klaten.